PENENTUAN PEMBUKAAN CABANG BARU TOKO SINAR RIZKY MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING ( SAW) - Narti fitrianti; Prajoko Prajoko; Lelah Lelah (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
For shop owners, deciding to open a new strategic branch is one of the main keys in establishing their business. In determining a good place will provide advantages for the shop owner. In determining a place, there are several ways that will be considered in an effort to develop its business and have criteria, these criteria will later become a consideration for choosing a strategic place. Deciding to open a new branch takes a long time because the criteria given may not meet the desired criteria. And in determining a place is not easy because you have to know the distance between one branch to another, so it requires a strategic and efficient place so that the shop owner can be accepted easily by a consumer. Therefore, to be more effective and efficient, a system is needed that functions to assist an entrepreneur in determining which place is suitable for occupancy. In this research, the method that will be used is Simple Addicie Wighting (SAW). The SAW method will process data by assigning a weight value to the criteria that will be used as a reference by making decisions after which a decision matrix value will be made based on the criteria. From the results of the study, it can be the best recommendation for the shop owner to establish a strategic place of business in accordance with the wishes of Sinar Rizky Stores. So using the SAW method, it has the highest rating value which is which area can be used as a place to open a new branch at the Sinar Rizky store. Keywords : Simple Addictive Weighting (SAW), Determination of New Branch Opening at Sinar Sizky Store